When do cancer patients regret their treatment decision?: A path analysis of the influence of clinicians’ communication styles and the match of decision-making styles on decision regret - Nicolai, Jennifer; Eich, Wolfgang; Bieber, Christiane (Patient education and counseling, 2016)
Objective - To test the influence of physician empathy (PE), shared decision making (SDM), and the match between patients’ preferred and perceived decision-making styles on patients’ decision regret. - Methods - Patients with breast or colon cancer (n=71) completed questionnaires immediately following (T1) and three months after a consultation (T2). Path analysis was used to examine the relationships among patient demographics, patient reports of PE, SDM, the match between preferred and perceived decision-making styles, and patient decision regret at T2. - Results - After controlling for clinician clusters, higher PE was directly associated with more SDM (β=0.43, p<0.01) and lower decision regret (β=−0.28, p<0.01). The match between patients’ preferred and perceived roles was negatively associated with decision regret (β=−0.33, p<0.01). Patients who participated less than desired reported more decision regret at T2. There was no significant association between SDM and decision regret (β=0.03, p=0.74). - Conclusion - PE and the match between patients’ preferred and perceived roles in medical decision making are essential for patient-centered cancer consultations and treatment decisions. - Practice implications - Ways to enhance PE and matching the consultation style to patients’ expectations should be encouraged.
Available online 2 December 2015
Gesehen am 31.10.2019